Creative Problem-Solving Learning Model Assisted With Multimedia To The Competency Of Science - Dewi, Made Rai Laksmi; Putra, DB Kt Ngr Semara (International Journal of Elementary Education, 2020)
The learning model and learning media are two components that cannot be separated from learning. The learning process that is carried out does not use media, and innovative models will affect science competence. Thus, research was conducted to examine the effect of the Creative Problem Solving model assisted by multimedia on students' science knowledge competency. This research is a type of quantitative research that is quasi-experimental with the nonequivalent control group design. The population used was all fourth-grade students totaling 468 students. The sampling was random sampling techniques with 32 students in the experimental group and 33 students in the control group. The data collection method used is the test method with the type of objective test in ordinary multiple-choice, then analyzed using the t-test. Based on the calculation results obtained tcount = 4,200 and ttable = 2,000 at the 5% significance level with dk = 63. This means tcount = 4,200> ttable = 2,000. This study concludes that there is an effect of the Creative Problem Solving model assisted by multimedia on the competence of science knowledge of grade IV elementary school students